Addressing challenges of transition from children's home to independence: Udayan Care's Udayan Ghars (Sunshine Children's Homes) & aftercare programme - Kiran Modi; Monisha Nayar-Akhtar; Sumedha Ariely; Deepak Gupta (Scottish Journal of Residential Child Care, 2016)
The L.I.F.E. Model (Living In Family Environment), is a model that attempts to create familial relationships, consistent living circumstances, and social/educational support systems necessary to move towards independent adulthood for orphaned and vulnerable children (OVC). In addition, the model addresses multiple losses, grief and related issues by employing attachment and trauma-based understandings to child rearing, while using positive psychology tools to encourage resilience and developmental growth. In the last 19 years, Udayan Care (located in New Delhi, India) through the Udayan Ghars Programme and Aftercare Services, has employed an evolved L.I.F.E. model for the children it cares for (Modi, Nayar-Akhtar, Gupta, & Karmakar, 2014). The model includes a family-like regulated support system, with long-term mentors who are set in place to help the children transition from institutional care to independent living. Typically, this takes place with the children moving out of the Sunshine Children's Homes into semi-regulated Aftercare services and then from Aftercare into the larger world. Given the normative transitions for all young persons, finding ways to effectively support institutionalised children as they transition to independent living is critical. In addition to the normative challenges, undoubtedly, institutionalised children come with a history of trauma and abandonment and often have long-term psychological difficulties that are unique to their population. Many such children end up in childcare institutions as there may be no extended family available, and the options for alternative care settings are severely limited. To understand the developmental trajectories of these children, Udayan Care has been participating in longitudinal research to describe the current and on-going changes in children's trauma, attachment, self-concept and ego-resiliency. This work has provided baseline information on the level and effectiveness of the programmes implemented at Udayan Care, and recommends future directions for addressing the children's needs. This paper explores the needs of institutionalised children as addressed by the Udayan Care Model. Such children have histories of severe neglect and need intensive efforts directed towards addressing attachment issues, affect dysregulation, behavioural difficulties, social skills, education and life skills training.